2018
DOI: 10.1155/2018/4197537
|View full text |Cite
|
Sign up to set email alerts
|

Gum Arabic Fibers Decreased Inflammatory Markers and Disease Severity Score among Rheumatoid Arthritis Patients, Phase II Trial

Abstract: Background Rheumatoid arthritis (RA) is autoimmune inflammatory disease that attacks the synovium of the joints. Both TNFa and interleukin-1 play crucial roles in the pathogenesis of RA. Gum Arabic (GA) is gummy exudates from Acacia senegal tree. Gum Arabic fermentation by colonic bacteria increases serum butyrate concentrations, so it is considered as prebiotic agent. Gum Arabic (GA) has anti-inflammatory activity through its derivative butyrate. To the best of our knowledge, this is the first study conducted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
47
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(50 citation statements)
references
References 35 publications
3
47
0
Order By: Relevance
“…Earlier studies reveled GA anti-inflammatory effects as it decreased several inflammatory markers as TNFα, ESR and CRP [19,20]. Reduction of CRP level could be accredited to GA prebiotics properties.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Earlier studies reveled GA anti-inflammatory effects as it decreased several inflammatory markers as TNFα, ESR and CRP [19,20]. Reduction of CRP level could be accredited to GA prebiotics properties.…”
Section: Discussionmentioning
confidence: 98%
“…It decreases the proinflammatory cytokine expression through inhibition of NFκB [16,17].Oral intake of GA has been shown to provide several health benefits [18], such as prebiotic effects [12]. GA has immune-modulatory [13,19], anti-inflammatory [20], and antioxidant properties [11,12,21,22].…”
Section: Introductionmentioning
confidence: 99%
“…The fermentation of acacia gum by colonic bacteria releases butyrate. Butyrate serves as a potent anti-inflammatory agent by inhibiting NF K B (it mediates the transcription of inflammatory cytokines) [50]. The improved anti-inflammatory activity of the synbiotic may be due to the combinatory use of acacia gum, and the TNF-α-level-lowering effect of acacia gum make it significant in patients with Crohn's disease and rheumatoid arthritis.…”
Section: Discussionmentioning
confidence: 99%
“…Tumor necrosis factor-α (TNF-α) is a main pro-inflammatory mediator involved in the development of RA (51) . Ebtihal et al (2018) demonstrated that the anti-inflammatory effect of GA through reduction TNF-α, erythrocyte sedimentation rate (ESR) level and improvement in clinical symptoms in RA patients when given (30 gm/day) of GA during the study period (52) .…”
Section: Anti-inflammatory Effectmentioning
confidence: 99%